2016
DOI: 10.1002/2211-5463.12138
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with adenylate cyclase toxin from Bordetella pertussis affects the metal binding properties of calmodulin

Abstract: Adenylate cyclase toxin domain (CyaA‐ACD) is a calmodulin (CaM)‐dependent adenylate cyclase involved in Bordetella pertussis pathogenesis. Calcium (Ca2+) and magnesium (Mg2+) concentrations impact CaM‐dependent CyaA‐ACD activation, but the structural mechanisms remain unclear. In this study, NMR, dynamic light scattering, and native PAGE were used to probe Mg2+‐induced transitions in CaM's conformation in the presence of CyaA‐ACD. Mg2+ binding was localized to sites I and II, while sites III and IV remained Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 32 publications
(71 reference statements)
1
15
0
Order By: Relevance
“…Independent experimental studies of calmodulin [ 31 ] reveal that the interaction of calmodulin with AC increases the apparent Ca binding in C-CaM. This is a close relationship to the observations of Selwa et al [ 21 ], as the involvement of R90 in hydrogen bond with AC and the displacement of CaM helices due to opening and closure of EF-hands [ 24 , 25 ] are directly connected.…”
Section: Interaction Between Calmodulin and Acsupporting
confidence: 66%
“…Independent experimental studies of calmodulin [ 31 ] reveal that the interaction of calmodulin with AC increases the apparent Ca binding in C-CaM. This is a close relationship to the observations of Selwa et al [ 21 ], as the involvement of R90 in hydrogen bond with AC and the displacement of CaM helices due to opening and closure of EF-hands [ 24 , 25 ] are directly connected.…”
Section: Interaction Between Calmodulin and Acsupporting
confidence: 66%
“…Site-specific mutations in the β-hairpin resulted in conformational perturbations in metal binding sites I and II of N-CaM, while no significant structural modifications were observed in C-CaM [ 56 ]. Intriguingly, when the AC domain interacts with intact CaM, the metal-binding sites I and II of CaM bind Mg 2+ ions, while the sites III and IV of CaM are loaded with Ca 2+ ions [ 57 ]. Mg 2+ ions are present in millimolar concentrations in the cytosol of cells and the action of CyaA and cAMP signaling induces entry of Ca 2+ ions into cells [ 28 , 58 , 59 ].…”
Section: Cyaa Structurementioning
confidence: 99%
“…The Ca 2+ -binding was monitored using 2D NMR to determine the amino proton-nitrogen chemical shifts for each amino acid residue mapping to metal binding sites I–IV in D22A. NMR chemical shift assignments were achieved by direct spectral comparison to previously reported values [ 20 , 21 ]. In the current study, we found that site-specific metal binding to D22A was evidenced by the direction and magnitude of amide proton-nitrogen chemical shift values observed in the presence of Ca 2+ -saturation ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is known that maximal enzymatic activity of CyaA is stimulated through interaction with both the N -terminal and C -terminal lobes of CaM [ 18 ]. Intermolecular association has been reported between N -terminal CaM and CyaA-ACD [ 19 ], and mutation in CyaA-ACD disrupts this low-affinity protein-protein binding interface [ 20 , 21 ]; however, it remains to be determined how activation of CyaA-ACD is achieved through association with both domains of CaM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation